Molecular Detection of Some Virulent Genes of Klebsiella Pneumonia in Pregnant Women with UTI - Khorshed, Aevar Ashraf (American Journal of Bioscience and Clinical Integrity, 2026)
Background & Aim: Klebsiella pneumoniae and Pseudomonas aeruginosa are responsible for most nosocomial UTI. Over the years, it is reported that the emergence of KD and PA resistance seemed to be rising. Objective: The present study was planned with an aim to delineate few virulent genes in K. pneumoniae among pregnant women. Report of the case and discussion Urinary tract infections (UTIs) are a common bacterial infection during pregnancy. Materials & methods: A total of 148 urine samples were obtained, which used clinically specimens from Kirkuk Hospital (Kirkuk city) between October 2024 and February 2025. The clinical samples were obtained after recruitment of the patients by the consultant urologist. The colonies of E. coli and K. pneumoniae on blood agar and MacConkey agar were identified by the morphological and biochemical characteristics, and then they were cultured and incubated at 37 ◦C for 24 h. Results: K. pneumoniae was detected in 27 (18.2%) of the 148 urine samples. The isolates exhibited high level resistance to Ampicillin (96.3%), Imipenem (81.5%) on the contrary, sensitivity was observed to Azithromycin (85.2) followed by Tobramycin and Amikacin 96.3% 100%, respectively). Of the 14 representative K. pneumoniae strains subjected to molecular analysis, 12 (85.7%) harbored the rmpA gene. Conclusions: Klebsiella pneumoniae was responsible for 18.2% of UTIs, showed high antibiotic resistance and all isolates harbored bssS and most exhibited rmpA genes associated with MDR, XDR and EDR phenotypes.